Free radicals activity of cassia surattensis / Sangetha, S. ... [et al.] - S, Sangetha; Z, Zuraini; S, Sasidharan; S, Suryani (2008)
A study is carried out to evaluate the free radical scavenging methanolic (MeOH) extract from the leave, flower, stem and pod of Cassia surattensis. Cassia surattensis leave, flower, stem and pod were collected, powdered and extracted with methanol by maceration at room temperature for 4 days. The extract was concentrated in a rotary evaporator. An amount of 1.Omg of each dry extract was dissolved in methanol and screened for their capabilities on scavenging of 2,2diphenyl-l-picrylhydrazyl radical (DPPH). The commercial antioxidant butylated hydroxytoluene (BHT, Sigma) was used for comparison or as a positive control. It was shown that all the methanol extracts of the samples tested were endowed with antioxidant activity. The free radical scavenging activity of the extract from flower and stem were higher than that present in the BHT a commercial antioxidant. The extract obtained from leave and pod showed a lower antioxidant activity compared with the commercial antioxidant. The present study shows the antioxidant effect of the Cassia surattensis. In this study, Cassia surattensis was identified as potentially novel sources of free radical scavenging compounds.